2012
DOI: 10.2466/24.22.pms.114.3.717-722
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Loudness Tolerance and the Acceptance of Background Noise for Young Adults with Normal Hearing

Abstract: This study investigated the relationship between listener loudness tolerance and listener acceptable noise level (ANL). Twenty-five normal hearing adults completed loudness tolerance and acceptable noise level measures. Loudness tolerance was measured using a scaling technique. The acceptable noise levels were calculated from a procedure designed to quantify a listener's willingness to accept background noise while listening to speech. Pearson correlation confirmed that loudness tolerance and acceptable noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Results of the present study are consistent those reported by Franklin et al (2012). Comparing results, the reported loudness tolerance of 75.4 dB HL (SD ¼ 9.3) differs from the 84.75 dB (SD ¼ 6.61) collected in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results of the present study are consistent those reported by Franklin et al (2012). Comparing results, the reported loudness tolerance of 75.4 dB HL (SD ¼ 9.3) differs from the 84.75 dB (SD ¼ 6.61) collected in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Both the acceptance of background noise and loudness tolerance are clinically valuable and should be performed on a regular basis when fitting patients with hearing aids (Kochkin et al., 2010). Previous research indicates a lack of any significant relationship between the acceptance of background noise while listening to speech and loudness tolerance for listeners with normal hearing (Franklin, White, & Franklin, 2012). However, this relationship has not been established in listeners with hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Although results from the present study revealed that those with high ANLs spend more time in less intense environments than those with low ANLs, the differences were not statistically significant. A different result may have been obtained with a larger sample, but this is unlikely, as Franklin et al (2012) and Crowley and Nabelek (1996) reported that the ANL is not related to loudness tolerance. Issues related to limited time for data collection and control over participant activities may be addressed in future studies.…”
Section: Discussionmentioning
confidence: 80%
“…The majority of research associated with the acceptance of background noise has focused on factors that may or may not influence the measure. Factors having little or no effect on the ANL measurement include, but are not limited to, age, gender, degree of hearing loss, loudness tolerance, and hearing-aid experience (Nabelek et al, 1991(Nabelek et al, , 2006Crowley and Nabelek, 1996;Rogers et al, 2003;Nabelek et al, 2006;Moore et al, 2011;Franklin et al, 2012). Factors known to affect the ANL include speech presentation level, medications related to attention disorders, digital noise reduction (DNR), and directional microphone technology (Freyaldenhoven et al, 2005(Freyaldenhoven et al, , 2007Franklin et al, 2006;Mueller et al, 2006).…”
mentioning
confidence: 99%
“…They reported similar LDL and ANL values to those reported in prior works, but also reported a lack of correlation between ANL and the LDL measurement and suggested that loudness discomfort (i.e., LDL) and loudness tolerance measures (i.e., ANL) capture different attitudes about noise. As suggested in previous reports (i.e., Mueller and Bentler, 2005;Franklin et al, 2012), the LDL may be clinically useful in determining hearing aid output limits. Because subjective satisfaction with hearing aids in loud, noisy environments is likely influenced by both comfort and intelligibility, the LDL may not be the best tool to evaluate hearing aid satisfaction.…”
mentioning
confidence: 73%